Impact of Succinylcholine vs. Rocuronium on Apnea Duration for Rapid Sequence Induction: A Prospective Cohort Study - Tang, Lijun; Zhao, Xiao; Li, Shitong; Huang, Lina; Li, Jinbao; Chen, Lianhua; Huang, Shiwei (Frontiers in Medicine, 2022)
Objective The present study aimed to evaluate the impact of 1.5 mg/kg succinylcholine or 1.2 mg/kg rocuronium, vs. 1.0 mg/kg succinylcholine on apnea duration in patients underwent rapid sequence induction (RSI). Methods This prospective cohort study was conducted in the Department of Anesthesiology in Shanghai General Hospital from July 2020 to November 2020. Apnea duration was defined as the time from apnea prompted by the PETCO2 waveform to the time the point of oxygen saturation declined to 90% (T90) and 95% (T95) after succinylcholine or rocuronium administration. The primary outcome included T90 and T95 changes in 1.5 mg/kg vs. 1.0 mg/kg succinylcholine groups and 1.5 mg/kg succinylcholine vs. 1.2 mg/kg rocuronium groups. Results A total of 265 participants were subjected for analysis. The succinylcholine (1.0 mg/kg) group had a significantly longer T90 (50.72, 95% confidence interval [CI, 7.60, 94.38], P = 0.015) and T95 (48.09, 95% CI [7.11, 89.07], P = 0.012) than the succinylcholine (1.5 mg/kg) group. In addition, significantly longer T90 (56.84, 95% CI [16.24, 97.44], P = 0.003) and T95 (50.57, 95% CI [12.58, 88.57], P = 0.003) were observed in the rocuronium (1.2 mg/kg) group than those in the succinylcholine (1.5 mg/kg) group. No severe side events were observed during the operation. Conclusion Rocuronium and the lower dose of succinylcholine may be recommended to patients underwent RSI.